The Nexus Between Quality Tourism and Sustainable Development Goals: Case Study of Uma Uta Tourism Village, Sikka Regency, NTT Province - Michael Rudolfus Sawu (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2024)
This research aims to analyze the development of quality tourism and the resulting impacts in order to provide social and economic justice in the tourist village.This research provides a critical perspective on the development of quality tourism and its associated impacts linked to sustainable development goals. This study adopts a qualitative research paradigm with a phenomenological approach. Data analysis techniques employed include: observation, in-depth interviews, and literature review.This research found that the impact generated from the development of quality tourism is still minimal. When researchers connect it with sustainable development goals, it can be understood that every aspect, including social, economic, environmental, and cultural, needs improvement. The local community has not yet massively benefited from tourism to improve their standard of living.